The mediating role of intrinsic capacity in balance and falls among older adults - Yao Cui; Jian Zhou; Qian Liu; Hui Ye; Bo Liu (Scientific Reports)
Abstract The intrinsic capacity (IC) and balance function of older adults are closely related to falls. IC is not only directly related to falls but may also play a mediating role in balance and falls. This study aims to explore the mediating role of IC in balance and falls. A total of 284 elderly patients were divided into fall group (n = 131) and non-fall group (n = 153) based on whether they had experienced falls. All patients underwent assessments of IC, including locomotion (SPPB), vitality (MNA-SF), sensory (self-reported vision/hearing), cognition (MOCA), and psychological status (SAS/SDS). Patients underwent the sensory organization test and limits of stability test. (1) Using fall history as a binary dependent variable and various balance indicators as independent variables, visual (VIS) (p = 0.011, OR 0.957), vestibular function (p < 0.001, OR 0.958), and direction control (p = 0.042, OR 0.967) were negatively associated with falls. (2) After incorporating IC scores, sensory function (p < 0.001, OR 0.154), SPPB (p = 0.003, OR 0.758), and SOT-Composite (p < 0.001, OR 0.900) were negatively associated with falls, while SAS (p = 0.008, OR 1.068) was positively associated with falls. (3) IC score mediated the relationship between movement velocity (MVL) and falls. Among the five dimensions of IC, the SPPB and the MNA-SF mediated the relationship between MVL and falls, and the SPPB mediated the relationship between maximum excursion (MXE) and falls. The SAS mediated the relationship between SOM, VIS and falls, while the SDS mediated the relationship between SOM, EPE and falls. There are multiple mediating effects of IC between balance function and falls.